Application of Organic Fertilizer to Shallot Yields in Various Mulches - Ir. Made Sri Yuliartini, M.Si; Ir. Luh Kartini, M.Si; Ir. Anak Agung Ngurah Mayun Wirajaya, MM; Dr. Ir. Ida bagus Komang Mahardika, M.Si; Dr. Ir. I Gusti Bagus Udayana M.Si (International Journal of Integrated Science and Technology, 2023)
Shallot is a superior commodity cultivated by farmers intensively, contains substances that are beneficial to health and is used as a cooking spice.. Utilization of waste and returning to organic can improve the environment where it grows so that the availability of nutrients can increase shallot crop yields. This study aims to find the type of organic fertilizer and mulch that gives high yields for shallots. . This research was a factorial experiment with a randomized block design (RBD) consisting of two factors, namely the type of organic fertilizer (J) consisting of 3 levels, namely 30 tons ha-1 rabbit manure (J1); chicken manure 30 tons ha-1 (J2) and organic fertilizer karambitan agro 30 tons ha-1 (J3) and the various types of mulch (M) consisted of 3 levels, namely straw mulch (MJ), husk mulch (MS), and plastic mulch (MP). The research was conducted in rice fields in Subak Sampalan Delod Margi, Dawan District, Klungkung Regency . The highest tuber fresh weight per clump and per hectare to be obtained in the 30 ton ha-1 rabbit manure treatment, namely 73,61 g and 7,36 tons, when compared to the lowest results in the 30 ton ha-1 chicken manure treatment ie weighing 44,90 g and 4,49 tons experienced an increase of 63,94% and 63,92%. The highest fresh weight of tubers per clump and per hectare were obtained from husk mulch, namely 67,50 g and 6,75 tons, which increased by 48,38% and 48,35%, compared to plastic mulch, namely 45,49 g and 4,55 tons.